STRATEGI GURU DALAM MENGEMBANGKAN PEMBELAJARAN SBdP PADA KREATIVITAS SISWA KELAS IV SD 2 MEJOBO KUDUS - Ahmad Ulil Albab; Darmawan Baihaqi; Wijayanto, Wasis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this research is to understand how teachers use SBdP learning to influence students' creativity at SD 2 Mejobo Kudus. The second objective is to understand and explain the factors that hinder the teacher's approach. This study uses a qualitative research approach. The purposive sampling technique was used by the data sources: Sample criteria were used to select participants. To test the validity of the data, method triangulation was used, such as observation, interviews, and documentation. Data obtained from interviews with teachers from Class IV A and B, research results on how teachers implement SBdP learning impact on the creativity of fourth-grade students, class teachers. choosing project-based learning strategies when teaching and the projects have already been created by the students. The results of the SBdP learning development, teacher preparation for teaching, such as preparing learning modules, preparing the materials to be taught, determining the projects to be made, scheduling the projects, tracking project progress, assessing project results, and evaluating SBdP learning using a projector. This research provides insights into the importance of teacher strategies and their inhibiting factors in the development of SBdP learning for the creativity of fourth-grade students. Internal factors are related to the experience, skills, and abilities of the teacher.